Thinking on the Correlation Between Bauhaus and Computational Design Education - Selin Oktan; Serbülent Vural (Journal of Contemporary Urban Affairs, 2019)
This study assesses that there are similarities between the Bauhaus movement and computational design. The similarities are discussed under the titles of hands-on activities, interdisciplinary studies and relation with technology for both Bauhaus and computational design. Digital technology is changing rapidly, and to catch the developing technology up the education system must be updated. Bauhaus can be a pathfinder for computational design education. Within this context, three educational organizations, KTU CODE FAB, IAAC and ICD, which were experienced personally, are examined. As a result of the study, it is reduced that; the innovative spirit of Bauhaus, which focuses on doing and hands-on activities, is also important for computational design education. The well-trained architects that accustomed to the new technology can be graduated with the integration with industry, similarly to the Bauhaus system.